Neuroprotective Potential of Cell-Based Therapies in ALS: From Bench to Bedside - Forostyak, Serhiy; Sykova, Eva (Frontiers in Neuroscience, 2017)
Motor neurons (MN) degeneration is a main feature of amyotrophic lateral sclerosis (ALS), a neurological disorder with a progressive course. The diagnosis of ALS is essentially a clinical one. Most common symptoms include a gradual neurological deterioration that reflect the impairment and subsequent loss of muscle functions. Up-to-date ALS has no therapy that would prevent or cure a disease. Modern therapeutic strategies comprise of neuroprotective treatment focused on antiglutamatergic, antioxidant, antiapoptotic, and anti-inflammatory molecules. Stem cells application and gene therapy has provided researchers with a powerful tool for discovery of new mechanisms and therapeutic agents, as well as opened new perspectives for patients and family members. Here, we review latest progress made in basic, translational and clinical stem cell research related to the ALS. We overviewed results of preclinical and clinical studies employing cell-based therapy to treat neurodegenerative disorders. A special focus has been made on the neuroprotective properties of adult mesenchymal stromal cells (MSC) application into ALS patients. Finally, we overviewed latest progress in the field of embryonic and induced pluripotent stem cells used for the modeling and application during neurodegeneration in general and in ALS in particular.